PEMODELAN DATA REKAM MEDIS DI RSUD TIDAR KOTA MAGELANG - , Tanti Dwi Wahyu Widiastuti, Dr. Wing Wahyu Winarno, MAFIS., Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
RSUD Tidar Kota Magelang is local hospital run by Magelang Country. The hospital already has a computerized information systems. This system is intended to record all data related to patients and all the treatments that the hospital provides, and to submit information needed by stakeholders. Unfortunately, since it still in the beginning phase of system development, only patients registration and basic medical records are covered by the system. Such a system was developed by external parties and even though the system meet the minimum requirement to be function, but it lacks of any documentation. Without any documentation, it is very difficult for the system designer to maintain and develop such a system. This study will develop data model for medical records at RSUD Tidar Kota Magelang, which is very important document in the system development. The data model will be developed using the data dictionary which refers to the data flow diagram. These components are needed in making data modeling based on the components identified in Health Care Information System Architecture (HCISA). Data modeling of medical records produces four types of data dictionary based on one of the DFD process created. Data modeling of medical records can provide detail information of medical records for IT personnel to manage better medical records and support the development of an integrated hospital information system.